Shiny Dashboard aplikace pro regresní analýzu - Osadcha, Tetiana; Malá, Ivana, 1962-; Malec, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The aim of this thesis is to present the Shiny Dashboard application which was written as a part of this work. The application allows user to perform the regression analysis on a given dataset. The first part of the thesis describes regression types which are implemented in the application. The practical part describes the results obtained from the application using two different datasets. It shows how the application can be used to analyse the data and provides a guideline for a user to do their own calculation.
Vedoucí práce: Ivana Malá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: statistika [obor dipl. práce]; diplomové práce; master's theses